The Development of Instructional Model Using Context Based Learning with Geographic Information System to Enhance Creative Problem Solving for Upper Secondary Students - Anantasuk, Nattawat; Kaewurai, Wareerat (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2023)
This research aims to develop a context based instructional model with geographic information system and to promote creative problem-solving abilities of upper secondary students. The research was carried out according to the research and development process in four steps which comprise: 1) studying the basic information for the development of instructional models; 2) building and checking quality; 3) studying the results of using the instructional model by applying it to the sample group including 21students in Mathayomsuksa 6 at Navamindarajudis Matchim School, and 4) evaluating the use of the instructional model. The findings were as follows: 1) The students’ creative problem-solving conditions at present were at a moderate level ( = 2.96, S.D. = 0.93), and the student’s creative problem-solving ability was 16.98 average score, representing 56.58 percent; 2) The development of the developed instructional model consists of: 1) principles, 2) objectives, 3) content, 4) teaching and learning process in 6 steps; 1) discover the problem from the context, 2) collect spatial data, 3) analyze the solution, 4) design the problem solving process, 5) display the result of the solution processing, 6) applied in context, and 5) measurement and evaluation. The results of the quality inspection were appropriate at a high level, having an Effectiveness Index (E.I.) of 0.71; 3) The students who were taught through the instructional model had the ability to solve problems creatively after studying at 70 percent higher than the threshold with a statistical significance at the .01 level, and 4) The students who were taught through the learning management had a high level of opinion on the instructional model ( = 4.13, S.D. = 0.62)